Yttrium and cobalt doped LaNiO3 nanoparticles synthesis and solar light driven photocatalytic removal of Rhodamine B. (March 2023) - Ghafoor, Aamir; Bibi, Ismat; Majid, Farzana; Ata, Sadia; Nouren, Shazia; Raza, Qasim; Mansoor, Samia; Alqahtani, Fatimah O.; Elqahtani, Zainab M.; Mehr-un-Nisa,; Iqbal, Munawar
Highlights: A series of Yttrium and Cobalt doped LaNiO3 were prepared by micro-emulsion route. Prepared samples were studied for structural, electrical, optical and catalytic properties. The photocatalytic activity was evaluated by degrading RhB dye. Yttrium and Co doped LaNiO3 have potential for dyes remediation under visible light irradiation. Abstract: La1-x Yx Ni1−y Coy O3 nanoparticles were fabricated via facile microemulsion route and impact of dopants was evaluated based on various structural, electrical and optical properties. The X-ray diffraction pattern confirmed the distorted rhombohedral symmetry with space group R3 c ¯ of La1-x Yx Ni1−y Coy O3 with particle size in 76–92 nm range. Dielectric parameters showed high dispersion at low frequency, while remained constant at low values. The AC conductivity showed increasing trend with doping in association with enhanced polarization. Band gap was tuned from 2.75 eV for pure LaNiO3 (LNO) to 2.60 eV for doped LNYC3 material in agreement with decline in PL intensity for improved catalytic response. The LNYC3 showed superior RhB degradation efficacy of 91% versus pure LNO (63%) in 210 min under visible illumination with rate constant of 0.0513 and 0.0029 min −1, respectively. In view of its promising catalytic activity, LNYC3 has potential application for the removal of dyes from effluents under solar light irradiation. Graphical abstract: Image, graphical abstract